Incurable Blackness: Criminal Disenfranchisement, Mental Disability, and the White Citizen - Dilts, Andrew (Disability Studies Quarterly, 2012)
The Maryland State Constitution states that its General Assembly may, "regulate or prohibit the right to vote of a person convicted of infamous or other serious crime or under care or guardianship for mental disability." In a single sentence, the link between criminality and mental disability is invoked in order to draw an internal boundary around those who can take part in the project of representative government. Through a close reading of one particular moment in the history of Maryland's disenfranchisement provisions, I show how these restrictions could buttress prevailing racial hierarchies. Delegates to Maryland's nineteenth century constitutional conventions explicitly understood disenfranchisement as a practice that managed the boundaries of full citizenship through the courts' power to determine criminal guilt and mental competence. In defining "exceptions" to the franchise, the delegates were additionally shoring up the increasingly unstable conception of whiteness. The figure of the "free negro" was persistently invoked to do this work, marked through criminality and insanity as civically disabled in order to both reduce the threat that s/he posed to the standing of white workers and to shore up the purity of whiteness itself as innocent, able, and fit to rule. In so far as disenfranchisement is an instrument of racial oppression, it continues to operate racially not just in spite of color-blind liberalism, but also precisely through its ability to disarm claims of racial animus. The norms that drove the adoption of disenfranchisement in the nineteenth century continue to ground these exclusions to the vote, meaning that the ideal figure of the American citizen continues to be compulsorily white, male, heterosexual, and able-bodied. Ending this legacy of social and political hierarchization requires that we remove disenfranchisement provisions, but also move beyond the logic of inclusion, divesting the vote as a location that finalizes, essentializes, and fixes the boundaries of the polity.